1999
DOI: 10.1002/j.1834-4453.1999.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

A radiocarbon chronology for the Eastern Lapita frontier in Tonga

Abstract: We present a series of 31 AMS radiocarbon dates on charcoal samples from six sites with eastern Lapita and Polynesian plain ware occupations in the Ha'apai Islands of Tonga. These dates indicate an initial Lapita settlement beginning no earlier than 2850 cal BP, with a rapid transition to a Polynesian plain ware phase by 2650 cal BP at the latest. Comparison of the Ha'apai chronology to radiocarbon dates from elsewhere in Tonga and in Western Polynesia suggests it may have wider application, with only plain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…Flenley and others (1999) examined two small swamps in Ha'apai on the islands of Ha'afeva and Foa for their potential to provide palaeoecological information applicable to Lapita and later archaeological sites investigated by Burley and colleagues (Burley 1994;Burley et al 1999Burley et al , 2001). The two swamps examined, Finemui (on Ha'afeva) and Lotofoa (on Foa), were most likely former lagoons within the atolls (Flenley et al 1999 Basal organics began to accumulate in Finemui Swamp about 5770 yr BP (Flenley et al 1999).…”
Section: Ha'apai Island Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Flenley and others (1999) examined two small swamps in Ha'apai on the islands of Ha'afeva and Foa for their potential to provide palaeoecological information applicable to Lapita and later archaeological sites investigated by Burley and colleagues (Burley 1994;Burley et al 1999Burley et al , 2001). The two swamps examined, Finemui (on Ha'afeva) and Lotofoa (on Foa), were most likely former lagoons within the atolls (Flenley et al 1999 Basal organics began to accumulate in Finemui Swamp about 5770 yr BP (Flenley et al 1999).…”
Section: Ha'apai Island Groupmentioning
confidence: 99%
“…Lapita culture has been documented on Tongatapu (Poulsen 1987;Burley and Dickinson 2001), Ha'apai (Burley 1994;Burley et al 1999) and Vava'u by about 2700-2800 yr BP (Burley and Connaughton 2007). European contact with Tonga was initiated by Dutch sailors in 1616 and by Abel Tasman in 1643 (Whistler 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few years ago, the latest of numerous minor revisions of Lapita colonization chronology suggested that the eastern region (Fiji and West Polynesia) was reached 2900-2800 B.P. (Anderson and Clark 1999;Burley et al 1999). Now it seems that the first Lapita colonists, bearing ceramics of Western Lapita design and New Britain obsidian, reached the region around 3000 B.P.…”
Section: Migration and Colonization In Remote Oceaniamentioning
confidence: 99%
“…It has been demonstrated that in Remote Oceania it generally lasted only 200-300 years (Anderson and Clark 1999;Bedford 2003;Burley et al 1999;Sand 1997). It is from about 2700 years ago that clear divergence in the archaeological record begins, suggesting a contraction or specialization of exchange, an increasing focus on local adaptation, sociopolitical transformation, and possibly secondary migrations by groups with a quite different cultural background (Spriggs 1997a: 152-161).…”
Section: Introductionmentioning
confidence: 99%